2019
DOI: 10.3892/ol.2019.11246
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑608 promotes apoptosis via BRD4 downregulation in pancreatic ductal adenocarcinoma

Abstract: The prognosis of pancreatic ductal adenocarcinoma (PDAC) remains poor even among patients with the same Tumor-Node-Metastasis stage. Thus, it is necessary to identify biomarkers that can accurately predict outcomes. There is accumulating evidence suggesting that microRNA (miR) expression influences overall survival (OS) time in patients with PDAC, via the regulation of tumor suppressor genes and oncogene expression. Specifically, miR-608 expression is hypothesized to regulate PDAC progression via the downregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Zheng et al, reported that expression of miR-4651 silenced BRD4 to inhibit non-small cell lung cancer (NSCLC) cell growth and proliferation [ 28 ]. Li et al, found that miR-608 induced pancreatic ductal adenocarcinoma cell apoptosis by silencing BRD4 [ 29 ]. Similarly, BRD4-targeting miR-608 inhibited HCC cell proliferation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al, reported that expression of miR-4651 silenced BRD4 to inhibit non-small cell lung cancer (NSCLC) cell growth and proliferation [ 28 ]. Li et al, found that miR-608 induced pancreatic ductal adenocarcinoma cell apoptosis by silencing BRD4 [ 29 ]. Similarly, BRD4-targeting miR-608 inhibited HCC cell proliferation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in pancreatic cancer, miR-608 is downregulated, and miR-608 can target ribonucleotide reductase M1 (RRM1) and cytidine deaminase (CDA) and control gemcitabine resistance ( 32 ). miR-608 also promotes PDAC cell apoptosis and prolongs PDAC patient OS by binding BRD4 ( 86 , 87 ) and AKT serine/threonine kinase 2 (AKT2). Therefore, miR-608 has the potential to act as a new diagnostic and prognostic marker and even a treatment target for pancreatic cancer.…”
Section: Dysregulation Of Mir-608 In Malignant Diseasesmentioning
confidence: 99%
“…Li et al. ( 86 ) revealed that miR-608 can decrease the level of BRD4 and facilitate cell apoptosis. However, in PDAC, miR-608 is usually significantly reduced.…”
Section: Dysregulation Of Mir-608 In Malignant Diseasesmentioning
confidence: 99%
See 2 more Smart Citations